2018
DOI: 10.1002/ldr.3035
|View full text |Cite
|
Sign up to set email alerts
|

The impact of grazing on seedling patterns in degraded sparse‐elm grassland

Abstract: Over‐grazing by livestock in semiarid ecosystems is one of the main causes of desertification. Although over‐grazing contributes to global environmental challenge, only a few studies have investigated grazing impacts on the composition of species and functional groups of seedling bank. In this study, we determined whether the composition of seedling species and functional groups, as well as the correlations between the seedlings of sparse‐elm (Ulmus pumila var. sabulosa or U. pumila) and other species changed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…Desertification in arid or semi-arid areas has been an environmental issue in regions as geographically diverse as Northern China, the Sahel, or the southwestern United States. [1][2][3] Desertification is associated with anthropogenic causes, 4 such as overgrazing, [5][6][7] logging, or unsustainable agricultural practices, 2,8 and climate change, 9 specifically shifts in the spatial and temporal patterns of rainfall [10][11][12] and gale days (wind velocity greater than 17 m/s). 13,14 When combined, these effects can lead to rapid vegetation cover loss, and subsequent wind erosion can also cause large dust storms, 15 leading to increased fine particulate air pollution with associated adverse health impacts 16,17 and desert encroachment onto vegetated and inhabited areas.…”
Section: Introductionmentioning
confidence: 99%
“…Desertification in arid or semi-arid areas has been an environmental issue in regions as geographically diverse as Northern China, the Sahel, or the southwestern United States. [1][2][3] Desertification is associated with anthropogenic causes, 4 such as overgrazing, [5][6][7] logging, or unsustainable agricultural practices, 2,8 and climate change, 9 specifically shifts in the spatial and temporal patterns of rainfall [10][11][12] and gale days (wind velocity greater than 17 m/s). 13,14 When combined, these effects can lead to rapid vegetation cover loss, and subsequent wind erosion can also cause large dust storms, 15 leading to increased fine particulate air pollution with associated adverse health impacts 16,17 and desert encroachment onto vegetated and inhabited areas.…”
Section: Introductionmentioning
confidence: 99%
“…In HG plots, mass emergence of seedlings in the early stages induced a sharp decrease in seedling density when temperatures increased and continuous drought occurred in June. In particular, the high seedling density resulted in high competition for resources (Ooi et al, 2014; Wang et al, 2018b). The initial conditions in hoof prints in HG possibly provided appropriate seed burial depth and a good temperature and moisture micro‐environment for seed germination in some plants.…”
Section: Discussionmentioning
confidence: 99%
“…Although grazing effects on seedlings have been examined in previous studies, the conclusions on whether grazing promoted or inhibited seedling emergence were inconsistent in different studies. Some studies suggested that grazing disturbance had a strong positive effect on seedling emergence and greatly increased the number of seedlings emerging (Eichberg & Donath, 2017; Watt & Gibson, 1988); however, other studies indicated that seedling number was low in heavily grazed grassland, and seedling density, species richness, and diversity reduced with intensive grazing (Gallacher & Hill, 2008; Wang et al, 2018b). These differing conclusions may be partly due to most studies paying more attention to the seedling emergence number and diversity at a specific period (Herrero‐Jáuregui & Oesterheld, 2018; Wang et al, 2018c).…”
Section: Introductionmentioning
confidence: 99%
“…Almost half of the sandy grasslands in China have been substantially degraded mainly due to overgrazing and conversion of grasslands to croplands (Li, Hao, et al, ; Wang et al, ). These degraded sandy grasslands can recover with natural restoration, but this is a very slow process (Li et al, ) due to the low water and nutrient holding capacity of soils and the limited nutrients (Zeng et al, ).…”
Section: Discussionmentioning
confidence: 99%